Impact of Anode heel effect on entrance surface dose of ovaries in lumbosacral spine radiography: phantom study - Sayed, Inayatullah Shah; Rahmat, Nur Izzah Syahira (2019)
Objectives: The aim of this research was to study the impact of heel effect on entrance surface dose (ESD) of ovaries in lumbosacral radiography with two orientations of the phantom in terms of tube axis.